(3YfOeG jCJj GdTJGAs - (3fjd, hGFds ((3GdbGgQIs (3OGQ Ohf ddfTQ hGdJhRjYs, 2018)
(3SfhGJ eQJ heQ HgG CTNGU de CYgOge ef GdZGFHjf(B, (3JQcJ CMdGkeG YOjOI Ydi CYJGH GdeMGhdGJ(B, (3JZjQJ edGeM hLgj hHQRJ HYV GdJLGYjO Hg(B, (3hHQRJ cKjQ ef GdefMfjGJ HbdHj hYbdj(B, (3GcJTaJ GdCSQGQ GdZGeVI aj faSj(B, (3hYdeJ Cf KeI CTNGkUG fdbGge aj RMGe GdMjGI bO jchfhG ajgG HYO fbWI QDjJfG GdhMjOI(B, (3hCf CTNGkUG cfG fJbGSe eYge GdMjGI bO dG jfJehf ajeG HYV Edi Cj HbYI ef GdCQV HGdfSHI dfG(B, (3JYdeJ HGdJLGQH GdJj cGfJ JMed HbShJgG CdeG eajkOG Cf SHjd GdfLGI de jcf aj GdBNQjf Hd cGf aj bdH jQJVj HeG JQchg ef eSGMGJ JSY ZjQge(B, (3hCf CMdGefG GdJj QCjfG ajgG edNU Gdchf hde Jcf dfG(B, (3cGfJ JOaYfG Edi CMdGe BNQi JfJXQ NWhGJfGs
10 12
Keywords: (3GdebGdGJ GdYQHjIs